Peran Penting Orang Tua dalam Mendukung Proses Pembelajaran Anak di Tingkat MI/SD - Rahmawati, Summayyah; Masyithoh, Siti (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Parents play a very important role in supporting children's learning process at the Madrasah Ibtidaiyah/Primary School (MI/SD) level. However, research on their concrete role in this context is still limited. The aim of this research is to explore more deeply the role of parents in supporting children's learning in MI/SD through analysis of relevant theoretical studies. The research method used involves a thorough literature study of theories that focus on the role of parents in children's education. The research results show that parents influence children's learning processes through emotional support, academic support, and active involvement in educational activities. The impact of an effective parental role includes increasing academic achievement, high learning motivation, and children's emotional and social well-being. The conclusions of this research highlight the importance of active parental involvement in children's education at the MI/SD level to achieve optimal learning outcomes. The practical implication of these findings is the need for further efforts to increase awareness and involvement of parents in their children's education at home and at school.